2016
DOI: 10.1021/jacs.6b04831
|View full text |Cite|
|
Sign up to set email alerts
|

Dual Targeting of Intracellular Pathogenic Bacteria with a Cleavable Conjugate of Kanamycin and an Antibacterial Cell-Penetrating Peptide

Abstract: Bacterial infection caused by intracellular pathogens, such as Mycobacterium, Salmonella, and Brucella, is a burgeoning global health epidemic that necessitates urgent action. However, the therapeutic value of a number of antibiotics, including aminoglycosides, against intracellular pathogenic bacteria is compromised due to their inability to traverse eukaryotic membranes. To address this significant problem, a cleavable conjugate of the antibiotic kanamycin and a non-membrane lytic, broad-spectrum antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 25 publications
5
107
0
Order By: Relevance
“…In another interesting experiment, kanamycin plus a cell penetration peptide (P14LRR) can release the antibiotic in a reduced cellular environment, leading to effective clearing intracellular pathogens ( Mycobacterium tuberculosis ) within macrophages. It is also effective in vivo against Salmonella in a Caenorhabditis elegans model [47*]. …”
Section: Application Strategies Of Antimicrobial Peptidesmentioning
confidence: 99%
“…In another interesting experiment, kanamycin plus a cell penetration peptide (P14LRR) can release the antibiotic in a reduced cellular environment, leading to effective clearing intracellular pathogens ( Mycobacterium tuberculosis ) within macrophages. It is also effective in vivo against Salmonella in a Caenorhabditis elegans model [47*]. …”
Section: Application Strategies Of Antimicrobial Peptidesmentioning
confidence: 99%
“…The anti-apoptotic protein Bcl-2 can inhibit ROS-induced lipid peroxidation by suppressing ROS production[24]. Studies have confirmed that Brucella infection can cause autophagy, inflammation, and apoptosis[25]; however, whether it is through the AIR domain or the ROS pathway has not been reported. Therefore, this study systematically explored whether the inflammation, autophagy, and apoptosis caused by Brucella infection is associated with the AIR domain and ROS pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the conjugate ( 90 ) protected by carboxybenzyl group (Cbz) (Figure ), was designed to measure the release of the kanamycin component from the disulfide‐containing conjugate by HPLC. These were of 1.5 ± 0.2 and 4 hours for half‐life and full release, respectively . The authors also showed that the ester bond of ( 87 ) was not susceptible to esterase enzymatic activity, probably due to steric hindrance of kanamycin around this ester bond (Figure ).…”
Section: Trojan Horse Approaches To Overcome Antimicrobial Resistancementioning
confidence: 95%
“…Like Mycobacterium, Salmonella , and Brucella are intracellular bacteria that reside inside mammalian host cells (eg, macrophages), where they reproduce and form a long‐term colonization, thus causing chronic and difficult‐to‐treat infections . Brezden et al recently reported interesting conjugates (Figure ), consisting of the aminoglycoside antibiotic kanamycin ( 85 ) with the CPP P14LRR ( 86 ), which when conjugated exhibited potent ATB activity against these intracellular pathogens . The CPP ( 86 ) previously demonstrated intrinsic ATB activity against intracellular Salmonella and Brucella bacteria .…”
Section: Trojan Horse Approaches To Overcome Antimicrobial Resistancementioning
confidence: 99%
See 1 more Smart Citation